Analisis SWOT Marketing MIX Pada SMA Muhammadiyah 1 Palangka Raya - Rima MEILINDA (FKIP, Universitas Palangka Raya, 2020)
This study aims to know: (1) the Marketing mix strategy on education service at SMA 1 Muhammadiyah Palangkaraya (2) a SWOT analysis to marketing mix strategy (product, price, place, promotion, people, physical evidence and process) at SMA Muhammadiyah 1 Palangka Raya. This study used qualitative descriptive approach, by using data collection method of observation, interview and documentation. The main informants of this study were principal, vice principal, students and parents of the students. The procedures of processing data were be started from the data reduction phase, data presentation, and conclusion/verification. Based on the results of the study: The appropriate marketing strategy was be applied to SMA Muhammadiyah 1 Palangka Raya, was the ST Strategy (strength and threats). This strategy had been applied where the strength of the school was used to overcome the threats that may be encountered in developing the product and building the image of product to the perspective of prospective students. This school tried to make the prospective students providing a positive response about the products that school offered. Building of Image was influenced by familiarities, familiarities was influenced by the amount of information that were received by new prospective students from the others personal experience or from the mass media. Utilizing the web information media or direct face-to-face services were the way to attract new students, in this way the school created a friendly and open impression to provide pleasure for prospective students. Then, the school provided information efficiently without reducing the quality of products related to religious education in SMA Muhammadiyah 1 Palangka Raya. The information referred here was to give the parents feeling calm and comfortable when they entrusted their children to study in SMA Muhammadiyah 1 Palangka Raya. The explaining information included that in this school beside teaching formal education also building the students’ aqidah, then in this school taught tadarus Al'quran for the students, which was useful to train the students in reading Al'quran, and instilling shalat on the time, when adzan zuhur reverberated all of the students obliged to the mosque to do shalat zuhur together.